Decompilation and copyright in ideas - the protection of non-literal elements of computer software and the idea/expression dichotomy - Jooste, Jacobus Petrus (Stellenbosch University, 2020)
The maxim, that copyright law does not protect ideas, is frequently challenged when the established principles are tested against new forms of expression or exploitation of a work. The evolution of computer programs, its unique characteristics and the increasing value of software as a commodity have resulted in a strained relationship between copyright law and the public interest regarding access to the underlying ideas in a computer program. This work examines the misalliance between copyright principles and the technical nature of computer programming, with a specific focus on the act of decompiling an existing program where it is undertaken in order to understand the underlying ideas and techniques. The impetus for this analysis is the sui generis classification of computer programs in South African copyright law and the potential this offers for development of domestic law in pursuit of national policy goals. This work conducts a normative analysis of the law and the technical reality of decompilation, from the perspective that copyright law must maintain a clear separation between the idea and the expression. The review of national and foreign copyright law is, throughout, conducted with a perspective on the effect of protection and a critical examination of the degree to which the law maintains an adequate balance between the private and public interests in the protection of software. In this respect, the current legal position is evaluated and a different, normative and prodevelopmental perspective regarding decompilation is proposed. It is submitted that are balancing of interests is justified and essential in order to establish an appropriate level of fairness and, at the same time, stimulate progress in this industry. It is argued that the act of using computer code to discover its meaning should not amount to infringement in the form of reproduction or adaptation of the work. It is found that the perception of decompilation, as a form of infringement, relies on an analogy to literary work. This view, it is argued, is ill suited to the nature of computer programs, at odds with the sui generis classification in SA copyright law, causes overbroad protection and violates the idea/expression separation. In light of the technical review of decompilation, it is found that the legal basis for prohibiting decompilation as a form of infringement is narrower than commonly assumed and that copyright law principles should be reinterpreted purposefully to permit decompilation. This work advocates that decompilation must be permissible and that an exemption, in SA copyright law, which is limited to decompilation for interoperability alone, is not appropriate in light of the national developmental agenda. Therefore, an alternative exemption is proposed which accommodates the technical reality of decompilation, the public interest in access to ideas and the commercial interests of copyright owners. This approach is supported by an analysis of international copyright law and is based on the inherent flexibilities of the three-step test. The justification for the findings of this work and the proposed departure from foreign precedent is supported by a close examination of the effect of a limited decompilation exception in foreign law and the impact of legislative measures to restrict circumvention of technological protection measures.
URI: http://hdl.handle.net/10019.1/109088
Keywords: Copyright; Copyright infringement; Decompilation; Intellectual property; International Copyright

Protecting the Industrial Designs of Today and the Future - Samoylov, Vladimir (Victoria University of Wellington, 2020)
This study examines and critiques New Zealand intellectual property protection for industrial designs, taking into account that many New Zealand industrial design owners outsource manufacture of their designs to China. Industrial design, which refers to improving the aesthetics of products to increase their marketability, is evolving conceptually and practically. In New Zealand, copyright and registered design laws each protect, respectively, the visual expression and the “eye appeal” of an original design. As design practices evolve with advances in technology however, it is increasingly evident that industrial design is about more than just visual expression or “eye appeal”. Many designers are not focusing solely on product stylisation and decoration, but on the provision of a more holistic product experience for the consumer. The development process of industrial designs from concept to marketable product is also changing, with many New Zealand industrial design owners employing increasingly efficient design development strategies. The fast-paced, cost-effective infrastructure of China is often utilised by New Zealand businesses for the manufacture of industrial designs. This study therefore sought to determine how to appropriately protect New Zealand industrial designs, in light of: a. foreseeable advances in technology; and b. the fact that many New Zealand industrial designs are manufactured in China. To answer these questions, this study examined and analysed New Zealand’s copyright and registered design laws, taking into account not only existing protections, but also factors that are likely to be of significant relevance in the future, such as the impact on industrial design from developments in 3D printing and virtual reality. The Chinese intellectual property regime for industrial designs was also examined because China is a major trading partner and often, as noted, the locus of manufacture. The study included an empirical investigation, in the form of interviews with designers and design academics as well as legal practitioners specialising in intellectual property law. The input of the interviewees, together with the legal analysis, informed a series of suggestions and recommendations for New Zealand policy and its law-makers regarding how industrial design protection can be improved. A key finding of this study was that existing legal protections do not appropriately protect increasingly holistic designs, as well as new types of designs emerging from developing fields such as virtual reality. In assessing the appropriateness of protection, the interests of industrial design owners were balanced against the public interest in protecting the public domain. It is suggested that to achieve equilibrium copyright law should be expanded to protect design expressions for all senses. Moreover, new categories of copyright protected works should be introduced to accommodate emerging design. The definition of design in registered design law should also be reconceptualised in order to acknowledge new types of designs and evolving design practices. Industrial design owners who outsource manufacturing to China can protect their designs via copyright as well as design patent. However, enforcement of intellectual property protection is unsatisfactory in many areas of China. Therefore, New Zealand industrial design owners should also employ non-legal protection strategies. Interviews with successful businesses, in the course of the empirical investigation for this study, revealed that the leveraging of existing relationships of those with already established operations in China, and intentionally splitting an industrial design’s component parts for manufacture among several factories in different locations, are useful strategies to employ.
Keywords: 3D printing; Artistic Craftsmanship; China; Copyright; Doing business in China; Intellectual property; Multisensory Designs; Propriedade intelectual; Propriété intellectuelle; Registered design; Spare Parts; Virtual Designs; Virtual Reality

Rights on news : expanding copyright on the internet - Furgal, Urszula (European University Institute, 2020)
The internet and digital technologies have irreversibly changed the way we find and consume news. Legacy news organisations, publishers of newspapers, have moved to the internet. In the online news environment, however, they are no longer the exclusive suppliers of news. New digital intermediaries have emerged, search engines and news aggregators in particular. They select and display links and fragments of press publishers’ content as a part of their services, without seeking the news organisations’ prior consent. To shield themselves from exploitation by digital intermediaries, press publishers have begun to seek legal protection, and called for the introduction of a new right under the umbrella of copyright and related rights. Following these calls, the press publishers’ right was introduced into the EU copyright framework by the Directive on Copyright in the Digital Single Market in 2019.
Accepted: 2020-02-20T11:26:15Z
Keywords: Copyright; Digital media; Electronic information resources; Intellectual property; Internet; Propriedade intelectual; Propriété intellectuelle

Protection of Intellectual Property Rights in International Trade - Indradewi, Anak Agung Sagung Ngurah (International Journal of Social Sciences, 2020)
That intellectual property is the creation of ideas in the form of new discoveries, literary works, and works of art, symbols, names and images used in trade. Of course, intellectual property is closely related to the world of commerce because its emergence is triggered by the desires of the members of the World Intellectual Property Organization who want to protect their economies in the era of free trade. In this case how the form of protection of intellectual property rights in the perspective of international trade, it can be seen that basically the laws and or regulations in every country in the world are different and each country has the right to implement its own legal rules in the jurisdiction of their country.
Keywords: Intellectual property; Intellectual property rights; International Trade; Legal rules